Acanthopagrus datnia (Hamilton, 1822), a senior synonym of Acanthopagrus longispinnis (Valenciennes, 1830) (Perciformes: Sparidae) - Hasan, Mohammad Eusuf; Durand, Jean-Dominique; Iwatsuki, Yukio (Zootaxa, 2020)
The taxonomic status of the Bay of Bengal nominal sparid species Coius datnia Hamilton, 1822 and Acanthopagrus longispinnis (Valenciennes, 1830) are reviewed and investigated both morphologically and genetically. Because of inadequate description and no type specimen, Coius datnia has recently been considered to belong to Sparidentex, a genus without molarifom teeth. Critical examination of the original description and examination of specimens from the type locality and adjacent areas reveal that Coius datnia belongs to Acanthopagrus, a genus with an inner series of molars. Furthermore, examination of specimens previously recognized as Acanthopagrus longispinnis (Valenciennes 1830), and recent collection of fresh specimens from lower Ganges estuary in Bangladesh, show that morphological differences between Acanthopagrus datnia and A. longispinnis are minor, and they are genetically identical. The longer second anal-fin spine in A. longispinnis (>21% SL) is, in fact, a feature of some younger A. datnia. Accordingly, A. datnia is regarded as a senior synonym of A. longispinnis, and is distinguished from its congeners by the presence of 12 dorsal-fin spines (rarely 11 or 13), 3½ scale rows between the fifth dorsal-fin spine base and lateral line, pelvic and anal-fins pale yellow to yellow with black streaks present in the interradial membranes of anal-fin rays, and caudal fin grey or yellowish grey. A neotype (and neogenotype) has been designated for Acanthopagrus datnia (Hamilton, 1822).